الوعي الوالدي بدور المختص الارطوفوني و علاقته بمستوى اكتساب اللغة الشفهية عند الطفل التوحدي دراسة ميدانية بالمركزين النفسيين البيداغوجيين بمدينتي افلو و الجلفة - عدنان رابحي; عبد القادر برماكي; سعدية زروق (My University, 2023)
This study aimed to know the parental awareness of the role of the orthophonist and its relationship to the level of verbal language acquisition of the autistic child. The descriptive approach was used, and the study was applied to a sample consisting of 18 autistic children and 18 of their parents . As for the tools, a questionnaire prepared for this purpose was used to measure parental awareness after arbitration, as well as the N.E.E.L test in its verbal aspect. As for the statistical treatment, the Pearson correlation coefficient was calculated, and after presenting and analyzing the results, the two researchers concluded that there was no statistically significant relationship between parental awareness of the role of the orthophonist and the level of verbal language acquisition of the autistic child